Career-changers' technology integration beliefs and practice in initial teacher education: A summative cross-case analysis. (2022) - Rowston, Kim; Bower, Matt; Woodcock, Stuart
Highlights: Technology use in prior roles increased reported confidence to integrate technology in teaching. Assistance needed to link technology skills from industry to curricula. Modelling and mentoring influenced technology integration beliefs and practice. External barriers during school placements impacted technology integration practice. Post-graduate initial teacher education programs need to adopt a more nuanced approach. Abstract: Fundamental to career-changers' successful transition into teaching is the design and delivery of post-graduate initial teacher education (ITE) programs. Career-changers enter teaching eager to share applied knowledge from prior occupations; however, support during ITE to facilitate the inclusion of these skills into teaching is often lacking. This study explored this phenomenon from a technology perspective and presents the outcomes of a cross-case analysis of four pre-service career-changers from an Australian university during ITE. Results indicated career-changers perceived their capacity to link existing technology skills to curricula depended on modelling and mentoring of technology integration during ITE subjects and school placements. School cultures combined with IT infrastructures also reportedly impacted technology practice. Recommendations to better support career-changers during ITE are discussed.